Hubungan Antara Kekuatan Otot Lengan, Kecepatan Gerak Dan Kelentukan Tubuh Dengan Dribel Bola Basket Pada Permainan Bola Basket Pada Tim Putri Smpn 2 Pandaan Kabupaten Pasuruan - Ruhut Ricardo Siringo Ringo; Siti Nurrochmah (Jurnal Porkes, 2026)
This study analyzes the relationship between arm muscle strength, movement speed, and body flexibility with basketball dribbling skills. A quantitative correlation approach was used with 40 athletes selected through purposive sampling. Data were collected using a standard push-up test for arm muscle strength, a 30 m sprint for movement speed, a sit-and-reach test for flexibility, and a zig-zag dribble test for skill assessment. The results showed a significant correlation between the three variables and dribbling ability, with movement speed showing the strongest relationship r=0.584, followed by body flexibility r=0.373 and arm strength r=0.137. Overall, these physical components explained 41.6% of the variation in dribbling skills R²=0.416. The analysis showed that movement speed contributed the most with a relative contribution of 46.1%, while arm strength contributed the least with 14.3%. These findings suggest that although all three physical aspects are important, training programs for adolescent female basketball players should emphasize the development of speed and increased flexibility to optimize dribbling performance.